1998
DOI: 10.1111/j.1471-0528.1998.tb10179.x
|View full text |Cite
|
Sign up to set email alerts
|

A role for noradrenaline in pre‐eclampsia: towards a unifying hypothesis for the pathophysiology

Abstract: Objective To compare plasma catecholamine (noradrenaline and adrenaline) levels in pre-eclamptic to normotensive pregnancy, and to study the activity of synthetic enzymes for catecholamines in placental and trophoblastic cell cultures. We postulated that catecholamines might be an important signal secreted by the fetoplacental unit in pre-eclampsia. MethodsWe recruited 12 women with pre-eclampsia and 12 pregnant women with nonproteinuric hypertension undergoing delivery by caesarean section, 23 normotensive wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…In previous studies, plasma catecholamine concentrations have been found to be increased in PRE pregnant women (4,25,26), and increased catecholamine secretion was supposed to be of placental origin (26). In our study, the PRE children tended to have slightly higher circulating E levels than the non-PRE children.…”
Section: Discussionsupporting
confidence: 64%
“…In previous studies, plasma catecholamine concentrations have been found to be increased in PRE pregnant women (4,25,26), and increased catecholamine secretion was supposed to be of placental origin (26). In our study, the PRE children tended to have slightly higher circulating E levels than the non-PRE children.…”
Section: Discussionsupporting
confidence: 64%
“…In previous studies, plasma catecholamine concentrations have been found to be increased in pregnant women with preeclampsia. [19][20][21] It was also noted that children exposed to preeclampsia have slightly higher circulating epinephrine levels than children born to normal mothers. 5 Recently, it has been found that young offspring of mothers with preeclampsia display marked vascular dysfunction in the systemic circulations and that this endothelial defect in the systemic circulation may contribute to the increased risk of arterial hypertension in the offspring.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Despite its relatively well-described pathophysiology, decades of intensive research, and its important consequences, the actual causes and the means to prevent the disease are still quite unknown. 1,2 Preeclampsia has been characterized as "a state of sympathetic overactivity," 3,4 which could be present already in the preclinical phase of the disease. 5 Psychosocial stress induces sympathetic arousal, activates the hypothalamic-pituitaryadrenal axis, and may thus promote endothelial dysfunction, 6 proinflammatory activity, 7,8 and blood pressure elevations.…”
mentioning
confidence: 99%